The Functional Fitness MOT Test Battery for Older Adults: Protocol for a Mixed-Method Feasibility Study. - De Jong, Lex; Peters, A.; Hooper, J.; Chalmers, N.; Henderson, C.; Laventure, R.; Skelton, D. (JMIR Publications, 2016)
BACKGROUND: Increasing physical activity (PA) brings many health benefits, but engaging people in higher levels of PA after their 60s is not straightforward. The Functional Fitness MOT (FFMOT) is a new approach which aims to raise awareness about the importance of components of fitness (strength, balance, flexibility), highlight benefits of PA, engages older people in health behavior change discussions, and directs them to local activity resources. This battery of tests combined with a brief motivational interview has not been tested in terms of feasibility or effectiveness. OBJECTIVE: To assess whether the FFMOT, provided in a health care setting, is appealing to older patients of a community physiotherapy service and to understand the views and perceptions of the older people undergoing the FFMOT regarding the intervention, as well as the views of the physiotherapy staff delivering the intervention. Secondary aims are to assess the feasibility of carrying out a phase 2 pilot randomized controlled trial of the FFMOT, in the context of a community physiotherapy service, by establishing whether enough patients can be recruited and retained in the study, and enough outcome data can be generated. METHODS: A mixed-methods feasibility study will be conducted in two physiotherapy outpatient clinics in the United Kingdom. A total of 30 physically inactive, medically stable older adults over the age of 60 will be provided with an individual FFMOT, comprising a set of six standardized, validated, age-appropriate tests aimed at raising awareness of the different components of fitness. The results of these tests will be used to provide the participants with feedback on performance in comparison to sex and age-referenced norms. This will be followed by tailored advice on how to become more active and improve fitness, including advice on local opportunities to be more active. Subsequently, participants will be invited to attend a focus group to discuss barriers and motivators to being more active, health behavior change, and the scope for individuals to improve their PA levels. To inform the design of a future trial, descriptive (eg, recruitment and retention rates), quantitative (Community Healthy Activities Model Program for Seniors; CHAMPS physical activity questionnaire), and qualitative data (focus group discussions, semi-structured staff interviews) will be collected. RESULTS: Recruitment and enrolment for the trial started in September 2015. Follow-up will be completed in June 2016. Results are expected to be available at the end of 2016. DISCUSSION: Allied health professionals play a key role in encouraging older adults to increase their PA, but with little evidence on how best to do this within their clinical practice. The purpose of this feasibility study is to examine the introduction of a new service: The FFMOT. The views and perceptions of the older people undergoing the FFMOT and relating to its delivery in clinical practice will be explored. Data, which will inform the feasibility of a randomized controlled trial of effectiveness of the FFMOT in promoting improved PA, will be reported. TRIAL REGISTRATION: International Standard Randomized Controlled Trial Number (ISRCTN): ISRCTN38950042; http://www.isrctn.com/ISRCTN38950042.